Candida glabrata prosthetic joint infection, successfully treated with anidulafungin: A case report and review of the literature. Issue 4 (19th January 2018) - Koutserimpas, Christos; Samonis, George; Velivassakis, Emmanouil; Iliopoulou‐Kosmadaki, Stylliani; Kontakis, Georgios; Kofteridis, Diamantis P.
Summary: Non‐ albicans Candida prosthetic joint infection (PJI) is extremely rare. A case of a Candida glabrata knee PJI is a 68‐year‐old splenectomised female smoker, suffering from chronic obstructive pulmonary disease (COPD) and alcoholism is reported. The patient presented with a peri‐prosthetic fracture, 15 years after total knee replacement surgery. Cultures of the intraoperative peri‐prosthetic tissue and materials yielded C. glabrata, as well as a methicillin‐resistant S. epidermitis . The patient was treated with anidulafungin and vancomycin. The knee prosthetic joint was removed and cement‐spacer with vancomycin and gentamycin was placed. Additionally, an external fixation was performed. A second stage revision surgery was planned, after completion of the antimicrobial and antifungal treatment. The patient is followed up for 4 months without signs, symptoms or findings of infection. PJI Candida infections require a high clinical suspicion index. It is of utmost importance to report these cases, since there is no consensus yet of the proper antifungal treatment. Furthermore, a literature review regarding treatment of those cases is provided. First‐line treatment with an echinocandin seems most proper, due to their fungicidal properties, their effectiveness against biofilm, as well as their minimal toxicity, making them ideal for long‐term use. Further experience is needed, for better understanding the disease's pathogenesis and optimal treatment.